Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Guru SMPN 7 Samarinda - Muhammad Mufid Prasetyo; Hudyah Astuti Sudirman; Asmadhini Handayani Rahmah (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to determine the influence of work motivation on teacher performance, the influence of the work environment on teacher performance, and the effect of work motivation and work environment together on the performance teachers of SMPN 7 Samarinda. This study uses a quantitative approach with a survey method. The sampling technique used is non-probability sampling with a saturated sample approach, namely the entire teacher population at SMPN 7 Samarinda totaling 47 people are used as research respondents. The results of this study show that work motivation has a significant effect on teacher performance, then the results of the work environment do not have a significant effect on teacher performance, and the final results show that work motivation and work environment together have a significant effect on the performance of teachers SMPN 7 Samarinda.